2014
DOI: 10.3233/jnd-140005
|View full text |Cite
|
Sign up to set email alerts
|

Forty-Five Years of Duchenne Muscular Dystrophy in The Netherlands

Abstract: Background: Duchenne muscular dystrophy (DMD) is a progressive muscle disease. No curative therapy is currently available, but in recent decades standards of care have improved. These improvements include the use of corticosteroids and mechanical ventilation. Objective: To present a detailed population based report of the DMD disease course in The Netherlands and evaluate the effect of changes in care by comparing it with an historical Dutch DMD cohort (1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…In total, 73% (11 of 15) of included studies were judged to have low risk of bias as measured using the Newcastle-Ottawa Scale (Table 1). Reasons for increased risk of bias included uncertain representativeness due to lack of details concerning confirmation of diagnosis of DMD [18], limited comparability due to inadequate description of ventilatory support [12,13,18], insufficient follow-up (with respect to the distribution of age in the studied patient sample) [26], and caregiver-reported age at death [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 73% (11 of 15) of included studies were judged to have low risk of bias as measured using the Newcastle-Ottawa Scale (Table 1). Reasons for increased risk of bias included uncertain representativeness due to lack of details concerning confirmation of diagnosis of DMD [18], limited comparability due to inadequate description of ventilatory support [12,13,18], insufficient follow-up (with respect to the distribution of age in the studied patient sample) [26], and caregiver-reported age at death [13].…”
Section: Resultsmentioning
confidence: 99%
“…Reports from several studies indicate that life expectancy at birth in DMD has improved in recent decades [9][10][11][12][13]. However, estimates vary markedly between samples, and, to date, no study has reviewed the body of literature on life expectancy in this indication.…”
Section: Introductionmentioning
confidence: 99%
“…The LUMC patients were recruited from the Dutch Dystrophinopathy Database. 21 Selected MRI results of this study have been previously reported. 13,22,23 The CCHMC participants were recruited from the international Prospective Natural History Study of Progression of Subjects With Duchenne Muscular Dystrophy (PRO-DMD-01) that started in 2012.…”
Section: Participants and Study Designmentioning
confidence: 94%
“…Twenty boys (8-18 years of age) with a mutation in the DMD gene were recruited from the Dutch Dystrophinopathy Database [21]. Seventeen healthy age-matched boys, without muscle or brain disorders, were recruited from local schools/leisure clubs using flyers.…”
Section: Methodsmentioning
confidence: 99%